Understanding Parenteral Behavior Changes Through Supplementary Feeding: A Small Group Discussion - Lina Mahayaty; Taufan Citra Darmawan; Retty Nirmala Santiasari; Niko Wahyu Prasetyo (KHD-Production, 2024)
Supplementary Feeding (SF) is a program providing additional food to groups in need of nutritional supplements, especially malnourished children. For malnourished children, food provision is one way to prevent growth and developmental problems. This study aims to evaluate the effect of health education on supplementary feeding using the SGD method on parental behavior. This research method employs a pre-experimental design with a One Group Pre-Post Test approach involving 32 parent respondents with children exhibiting poor or inadequate nutrition status at the Integrated Health Post for Toddlers “Posyandu Balita”. This research use Parrent Behaviour Questionnaire (PBQ). The PBQ is a 38 item self-report instrument which assesses the importance of specific parenting behaviors, this questionnaire showing a valid and reliable (Cronbach’s α > 0.7) structure. The Wilcoxon Test yielded a result of p = 0.000021 with a significance level of p < 0.05, indicating an impact on parental behavior in providing SF at the Integrated Health Post for Toddlers. Health education through the SGD method enhances parental understanding of the importance of SF consumption for toddlers. Through the SDG method, parents can share experiences and increase awareness of the importance of providing supplementary feeding, particularly to toddlers experiencing malnutrition. It is hoped that this research will encourage parents to be more proactive in meeting the nutritional needs of their children.